IMPLICATIONS OF FINANCIAL RATIOS IN STOCK PRICE EVALUATION - Setiyo Adi (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
The aim of the research is to determine the position of share prices in measuring debt. to Equity Ratio , return on equity and Earning Per Share . The data used are the financial reports of the Food and Beverage sub-sector companies for the period 2020-2023. The findings of the research results show that DER and ROE partially have no effect on stock prices. Other findings show that stock prices can be influenced by the Earning Per Share variable .